Perancangan Pembatas Interaksi sebagai Penunjang Kegiatan Bertransaksi di Kasir pada Masa New Normal - Andrianto, Andrianto; Chalik, Chris (Waca Cipta Ruang, 2021)
The current condition of the community is being faced with a pandemic outbreak which could be exposed to interaction activities between one human and another, one of them is transacting at the cashier. The need for transactions is difficult to avoid, so a design is needed that can minimize the spread of the virus while creating a sense of security and comfort for its users when carrying out these activities. The interaction barrier is a partition or divider that can limit one side to another which can be a solution to this problem. Using qualitative methods to identify and analyze visitor needs when transacting during the pandemic, this design begins with conducting interviews and observations of users when carrying out transactions at the cashier as initial data to formulate problems which are then developed based on theories related to color, shape and materials to analyze existing design needs. The design result is a functional interaction barrier which emphasizes the aspects of shape and color according to the needs of transaction activities at the cashier facility to help users stay healthy, free from the risk of being exposed to germs and viruses. The results of this design are also expected to be a reference for a study as well as a design reference with a similar theme in order to minimize the spread of the virus during the pandemic and the new normal period.